Pelatihan Da’i Anti Narkoba Desa Aek Bange Kecamatan Aek Ledong - Ismail Nasution (peduli riset dan pengabdian masyarakat, 2022)
Preaching is a noble task in the view of Allah Subhanahu Wata'ala, so that with this da'wah Allah has assigned the title of khoiru ummah (the best of the people) to the people of Muhammad Shalallahu 'Alaihi Wassallam. Imam Abu Hamid bin Muhammad al-Ghazali in the book Bidâyatul Hidâyah explains that the human tongue consists of two types, namely the tongue in the mouth and the tongue in the form of a qalam (pen). Observing the current development of drug distribution and use, shows that drugs have directly threatened the future of the younger generation. According to the analysis after observing the need for anti-drug preacher training activities targeted at youth who live in the village and may also be followed by teenagers from neighboring villages who want to follow it, the drug problem must exist in Aek Bange village according to a temporary assumption after observations were made that there are also those who use drugs in the village. Therefore, what is needed for a preacher who is actually a youth to take part in it must be an ustadz or a teenage preacher who can directly deal with users because the average user is youth, as well as the energy to be used as filler for Friday sermons in the mosques that are there must be able to give sermons. the dangers of drugs because drugs are very dangerous for youth and students in Aek Bange village.